EPIDEMIOLOGICAL AND CLINICAL FEATURES OF COMBINED RESPIRATORY INFECTIONS IN CHILDREN - V. V. Shkarin; A. V. Sergeeva (LLC "Diagnostics and Vaccines", 2017)
Presents a review of publications on the problem of combined respiratory infections among children. Viral-bacterial associations are registered  in a group of often ill children in 51.7%. More than half of the patients have herpesvirus infection in various combinations. The presence of a combined acute respiratory viral infection among children in the group from 2 to 6 years was noted in 44.2% of cases, among which, in addition to influenza viruses, RS-, adeno-, etc., metapneumovirus and bocavirus plays an important role.The increase in severity of acute respiratory viral infection with combined  infection, with chlamydia  and mycoplasma infection is shown. A longer and more severe course of whooping cough was observed when combined with respiratory viruses.The revealed facts of frequency of distribution of combined  respiratory infections in children, the severity and duration of their course with the development of various complications and the formation of chronic pathology dictate the need to improve diagnosis and treatment tactics of these forms of infections.